Blind spheres of paramagnetic dopants in solid state NMR. Issue 19 (7th May 2019) - Li, Wenyu; Zhang, Qianyun; Joos, Jonas J.; Smet, Philippe F.; Schmedt auf der Günne, Jörn
Abstract : Paramagnetic dopants make the NMR spectroscopist go blind in a sphere around a paramagnetic ion. How big is the blind zone? Abstract : Solid-state NMR on paramagnetically doped crystal structures gives information about the spatial distribution of dopants in the host. Paramagnetic dopants may render NMR active nuclei virtually invisible by relaxation, paramagnetic broadening or shielding. In this contribution blind sphere radii r 0 have been reported, which could be extracted through fitting the NMR signal visibility function f ( x ) = exp(− ar 0 3 x ) to experimental data obtained on several model compound series: La1− x Ln x PO4 (Ln = Nd, Sm, Gd, Dy, Ho, Er, Tm, Yb), Sr1− x Eu x Ga2 S4 and (Zn1− x Mn x )3 (PO4 )2 ·4H2 O. Radii were extracted for 1 H, 31 P and 71 Ga, and dopants like Nd 3+, Gd 3+, Dy 3+, Ho 3+, Er 3+, Tm 3+, Yb 3+ and Mn 2+ . The observed radii determined differed in all cases and covered a range from 5.5 to 13.5 Å. While these radii were obtained from the amount of invisible NMR signal, we also show how to link the visibility function to lineshape parameters. We show under which conditions empirical correlations of linewidth and doping concentration can be used to extract blind sphere radii from second moment or linewidth parameter data. From the second moment analysis of La1− x Sm x PO4 31 P MAS NMR spectra for example, a blind sphere size of Sm 3+ can be determined, even though the visibility function remains close to 100% over the entire doping range. Dependence of the blind sphere radius r 0 on the NMR isotope and on the paramagnetic dopant could be suggested and verified: for different nuclei, r 0 shows a -dependence, γ being the gyromagnetic ratio. The blind sphere radii r 0 for different paramagnetic dopants in a lanthanide series could be predicted from the pseudo-contact term.